Eugenol in combination with lactic acid bacteria attenuatesListeria monocytogenesvirulencein vitroand in invertebrate modelGalleria mellonella. Issue 6 (June 2016) - Upadhyay, Abhinav; Upadhyaya, Indu; Mooyottu, Shankumar; Venkitanarayanan, Kumar
Abstract : N/A: Listeria monocytogenes is a human enteric pathogen that causes severe foodborne illness in high‐risk populations. Crossing the intestinal barrier is the first critical step for Listeria monocytogenes infection. Therefore, reducing L. monocytogenes colonization and invasion of intestinal epithelium and production of virulence factors could potentially control listeriosis in humans. This study investigated the efficacy of sub‐inhibitory concentration (SIC) of the plant‐derived antimicrobial eugenol, either alone, or in combination with five lactic acid bacteria (LAB), namely Bifidobacterium bifidum (NRRL‐B41410), Lactobacillus reuteri (B‐14172), Lactobacillus fermentum (B‐1840), Lactobacillus plantarum (B‐4496) and Lactococcus lactis subspecies lactis (B‐633) in reducing Listeria monocytogenes adhesion to and invasion of human intestinal epithelial cells (Caco‐2). Additionally, the effect of the aforementioned treatments on Listeria monocytogenes listeriolysin production, epithelial E‐cadherin binding and expression of virulence genes was investigated. Moreover, the in vivo efficacy of eugenol‐LAB treatments in reducing Listeria monocytogenes virulence in the invertebrate model Galleria mellonella was studied. Eugenol and LAB, either alone or in combination, significantly reduced Listeria monocytogenes adhesion to and invasion of intestinal cells ( P < 0.05). Moreover, eugenol‐LAB treatments decreased Listeria monocytogenes haemolysin production, E‐cadherin binding and virulence gene expression ( P < 0.05). In addition, the eugenol‐LAB treatments significantly enhanced the survival rates of G. mellonella infected with lethal doses of Listeria monocytogenes ( P < 0.05). The results highlight the antilisterial effect of eugenol either alone or in combination with LAB, and justify further investigations in a mammalian model.